Trends in exposure to respirable dust and respirable crystalline silica among lithium mine workers in Western Australia - Gbondo, David; Zhao, Yun; Pham, Minh; Rumchev, Krassi (Elsevier, 2024)
Background: Exposure to respirable dust (RES) and respirable crystalline silica (RCS) is common in mining operations and is associated with health effects such as pneumoconiosis, chronic obstructive pulmonary disease (COPD), interstitial pulmonary fibrosis, silicosis, lung cancer, and renal disease. Methods: This study used industry occupational exposure data for respirable dust from two surface lithium mines in Western Australia for the period between 2017 and 2023. A total of 1122 samples were collected in workgroups across four departments - administration and support, mining, crushing and processing, and maintenance.